The role of artificial intelligence (AI) in transforming banking services For people with disabilities in the Kurdistan Region between challenges and opportunities - ڕشید, میران بێستون احمد (Sulaimani Journal for Humanities, 2025)
This paper examines the role of artificial intelligence (AI) in improving banking services for people with disabilities in the Kurdistan Region. It explores how AI can address the challenges in access faced by people with disabilities, as well as finding solutions The study highlights barriers such as lack of inclusive infrastructure, limited awareness among financial institutions, and lack of regulatory frameworks that support access. It also discusses the opportunities AI offers to create a more inclusive financial environment. The paper concludes with recommendations for banks, governments and technology developers to collaborate and implement AI solutions that ensure equal access to banking services for all. Importance of banking services Banking services are the backbone of modern economies, enabling individuals and businesses to manage their finances efficiently. They provide essential services such as savings, loans and money transfers along with promoting financial inclusion and economic growth Role of AI in Banking Services Artificial intelligence (AI) is revolutionizing banking by automating processes, improving efficiency and enhancing the consumer experience . Powerful AI tools enable personalized financial advice, fraud detection and faster transaction processing. Especially for people with disabilities, by removing physical barriers. What conclusion did we reach? Yes, artificial intelligence plays an important role in making banking services easier for people with disabilities.